Social Pedagogy and Social Education in Colombia: A shared Institutional, Academic and Professional responsability needed for social transformation - Francisco José Del Pozo Serrano; Cinthia Milena Astorga Acevedo (FahrenHouse, 2018)
In this article we pretend to reinforces and solidifies the idea of professionalizing the Social Education as a career and important alternative to respond to the challenges, dynamics and current needs of the Colombian context. To develop the above idea, first is performed a theoretical and/or conceptual delimiting of the Social Education as an object of study Social Pedagogy. Then, we present the potential and limitations by which this crosses on the path toward its institutionalization. Afterwards, we present the different areas of intervention and main intersectoral and legislative organisms; and finally, we shared the proposal that we consider is more pertinent as academic program of Social Education with emphasis and the set of degrees of socio-educational fields approved by the Ministerio de Educación Nacional in the 2016. Definitively, it turns out indispensable deepen efforts and co-responsibility in order that the proposals of this kind does not just remain on paper, but can be settled in reality, and are continued stimulating initiatives that promote the Social Education as a transformative element from the socio-educational action.